Objective assessment of goal orientation, time management and learning outcomes - Romero, Miriam; Juola, James; Casadevante, Cristina; Hernández, José Manuel (Anales de Psicología / Annals of Psychology, 2022)
Behaviors directed to achieving goals and managing tasks in a set period of time play important roles when people engage in learning activities. These behaviors, labeled goal orientation and time management, have been widely studied as part of self-regulated learning models. Previous works have traditionally employed self-reports to study these variables. However, these subjective methodologies suffer from limitations, and some researchers highlight the advantages of using objective measures. In the present work, we employ objective tests to study goal orientation, time management and their relation to learning outcomes. We propose a model and employ structural equation modeling to examine the hypothesized relations. The results provided a good fit to the data. Goal orientation (mastery) has a direct effect on time management, and both variables have direct effects on scores in a learning task. Time management also has a direct effect on academic performance. Theoretical and practical implications are discussed.